Clinical and Cure Profile of Tinea Capitis Patients - Noviannisa, Farah Ayu; Astari, Linda; Alimsardjono, Lindawati (Faculty of Medicine, Universitas Airlangga, 2022)
Background: Tinea capitis (TC) is a superficial mycoses infection of hair follicles and hair shaft caused by dermatophytes of the genus Trichophyton and Microsporum. Tinea capitis can cause hair loss and scales with varying degrees of inflammatory response. The incidence varies depending on geographical location and factors that affect the incidence rate. It is important to know the incidence also the clinical and cure profile of tinea capitis to provide benefits in the prevention, diagnosis, and treatment. Purpose: To evaluate the clinical and cure profile of TC patients at the Dermatology and Venereology Outpatient Clinic of Dr. Soetomo General Academic Hospital Surabaya from January 2019 to January 2020. Methods: A retrospective descriptive study based on medical records with a total sampling technique. Result: Of the 10 TC patients, who were the research subjects, TC predominantly affected males and at 5–11 years age group. The highest risk factor was a history of contact with cats. Scales were the most common clinical feature. Microsporum canis was the most common causative species, ectothrix arthrospores was revealed during the direct microscopic examination, Wood lamp's fluorescence was mostly yellow-green, and cigarette-shaped hair was the most common dermoscopic finding. Eighty percent of subjects were diagnosed with gray patch type. Conclusion: The diagnosis of TC was established based on the patient's history, clinical examination, and supporting examination.